Estimasi Dampak Jangka Panjang Kebijakan Penurunan Emisi Terhadap Pertumbuhan Ekonomi Kalimantan Timur - Hidayanty, Nurul Ilma; Herliansyah, Riki; Azka, Muhammad (Jurnal Matematika; Vol 9 No 1 (2019), 2019)
Deforestation and forest degradation issue due to economic activity is a major problem in East Borneo. The results of data analysis from Environmental Agency stated East Borneo produced the biggest ammount of CO2 emissions after the Central Borneo and Riau. These emissions mostly come from land-based business sector, industry and transportation. In other side, these sectors are the highest contributor to the total number of Gross Domestic Regional Product (GDRP). The aim of this research is to identify the effect of the goverment policy to decrease CO2 emissions towards economic growth. The data in this research were analyzed using Principal Component Analysis (PCA) and Path Analysis (PA). The results showed that the decrease in the amount of CO2 emissions resulting in decrease in the amount of GDRP. Keywords : CO2 Emissions, Gross Domestic Regional Product (GDRP), Principal Component Analysis, Path Analysis.